2017
DOI: 10.3126/jnhrc.v15i2.18158
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intravenous Ferric Carboxy-maltose in Pregnant Women with Iron Deficiency Anaemia

Abstract: Background: Iron deficiency is a common nutritional deficiency amongst women of childbearing age. Peri-partum iron deficiency anaemia is associated with significant maternal, foetal and infant morbidity. Current options for treatment include oral iron, which can be ineffective and poorly tolerated, and red blood cell transfusions, which carry an inherent risk and should be avoided. Ferric carboxymaltose is a modern treatment option. The study was designed to assess the safety and efficacy of intravenous ferric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…They concluded that intravenous ferric carboxymaltose was safe and effective in pregnant women with iron deficiency anaemia. (7) In our study, there was hypersensitive reaction. The incidence was 30% in our study.…”
Section: Baselinesupporting
confidence: 45%
“…They concluded that intravenous ferric carboxymaltose was safe and effective in pregnant women with iron deficiency anaemia. (7) In our study, there was hypersensitive reaction. The incidence was 30% in our study.…”
Section: Baselinesupporting
confidence: 45%
“…In second and third trimesters, IV iron therapy is safe and generally favored over oral formulations due to fewer side effects and rapid correction of anemia . Ferric carboxymaltose is commonly used when treating second and third‐trimester pregnancy IDA given its comparable safety profile to iron sucrose while requiring fewer repeated applications due to higher iron dose with each administration . Since hypophosphatemia is a known side effect of ferric carboxymaltose, care should be taken to mitigate any exacerbating factors like vitamin D deficiency .…”
Section: Iron Deficiency Anemia In Pregnancymentioning
confidence: 99%
“…53,54 Ferric carboxymaltose is commonly used when treating second and third-trimester pregnancy IDA given its comparable safety profile to iron sucrose while requiring fewer repeated applications due to higher iron dose with each administration. [55][56][57] Since hypophosphatemia is a known side effect of ferric carboxymaltose, care should be taken to mitigate any exacerbating factors like vitamin D deficiency. 58 Data are increasing on the safety of other formulations in pregnancy including low-molecular-weight iron dextran.…”
Section: Iron Defi Cien C Y Anemia In Preg Nan C Ymentioning
confidence: 99%
“…The side effect includes metallic taste, anaphylaxis, nausea, dizziness and local irritation. 4,5 Ferrous carboxymaltose (FCM) FCM was FDA approved in 2004. The single dose of Iv FCM, not exceeding 1500 mg of iron (30 ml) per day was given.…”
Section: Iron Sucrose (Is)mentioning
confidence: 99%